Turkey : 2007 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Turkey. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
The staff report for the 2007 Article IV Consultation highlights Turkey's economic revival and policies to entrench macroeconomic stability. Turkey has experienced an impressive economic revival in recent years. Exports have continued to gain market shares, as the effects of an appreciating currency have been largely offset by productivity gains. Executive Directors considered that Turkey needs to manage vulnerabilities carefully and address structural challenges to increase the economy's growth potential and resilience to shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet